Services Development and Comparative Advantage in Manufacturing - Liu, Xuepeng; Mattoo, Aaditya; Wang, Zhi; Wei, Shang-Jin (World Bank, Washington, DC, 2018)
Most manufacturing activities use inputs from the financial and business services sectors. But these services sectors also compete for resources with manufacturing activities, provoking concerns about de-industrialization -- financial services in industrial countries like the United States and the United Kingdom, and business services in developing countries like India and the Philippines. This paper examines the implications of services development for the export performance of manufacturing sectors. It develops a methodology to quantify the indirect role of services in international trade in goods and constructs new measures of revealed comparative advantage based on domestic value added in gross exports. The paper shows that the development of financial and business services enhances the revealed comparative advantage of manufacturing sectors that use these services intensively but not that of other manufacturing sectors. It also finds that a country can partially overcome the handicap of an underdeveloped domestic services sector by relying more on imported services inputs. Thus, lower services trade barriers in developing countries can help to promote their manufacturing exports.